The dynamics of household location preferences in Germany - Uwe Neumann; Christoph M. Schmidt (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Inspired by the literature on social polarisation and residential segregation we draw on a probabilistic approach to pursue the evolution of household location preferences in West Germany. Using microdata from the German Socio-Economic Panel (SOEP) for the period 1984-2020 we demonstrate that structural economic change was accompanied by an increasing preference for residence in compact housing close to urban centres. Our analysis outlines that during the past two decades, intra-urban and urban-rural disparities by age and skills have begun to rise. Even for Germany, where segregation is moderate, any scenario suggesting neighbourhood-level convergence of living standards seems unlikely. – – Anknüpfend an die Literatur über soziale Polarisierung und Segregation verfolgen wir mit Hilfe eines probabilistischen Ansatzes die Entwicklung der Standortpräferenzen von Haushalten in Westdeutschland. Anhand von Mikrodaten des Sozio-oekonomischen Panels (SOEP) für den Zeitraum 1984-2020 zeigen wir, dass der wirtschaftliche Strukturwandel mit einer zunehmenden Präferenz für das Wohnen in kompakten, zentrumsnahen Wohnungen einherging. Unsere Analyse verdeutlicht, dass in den letzten zwei Jahrzehnten die innerstädtischen und Stadt-Land-Unterschiede nach Alter und Qualifikation zugenommen haben. Selbst für Deutschland, wo die Segregation nur moderat ausgeprägt ist, erscheint eine Angleichung des Lebensstandards auf der Stadtteilebene unwahrscheinlich.
Keywords: C25; R21; R23; 330; Household location; segregation; structural change; SOEP